Analisa Rancang Bangun Sistem Informasi Penerimaan Kas Terhadap Toko Serba Guna Mebel - Hidayatulloh, Taufik; Syabaniah, Rifa Nurafifah; Marsusanti, Eva; Dewi, Lisnawati; Ismunandar, Dinar (Swabumi, 2019)
This research was conducted by analyzing three variables, this research variable consisted of three types of variables including; independent variables (information system design), furniture shop dependent variables and moderator variables (cash receipts). The purpose of this study was to find out the effect of the design of the design of the cash receipt information system on the Sukabumi district furniture store. The research discussion focused on three variables and was processed using a questionnaire microsoft excel application and Spss 20 that was shared with employees of a furniture store. Based on the results of the questionnaire analysis, it was found that there was an influence on the design of the cash receipt information system for the Sukabumi district furniture store in terms of the cash receipt process that was made for the problems that occurred in the furniture store, evidenced by testing validity tests using Microsoft Excel with results Pearson correlation> 0.5 and reliability test> 0.6 using SPSS 20. The future expectation of the research is to proceed with analysis of variable testing and program implementation.